Improving the quality of life of palliative and chronic disease patients and carers in remote Australia with the establishment of a day respite facility - Carey, Timothy A. (BMC Palliat Care, 2016)
BACKGROUND: In the Northern Territory (NT) there is a lack of respite services available to palliative care patients and their families. Indigenous people in the NT suffer substantially higher rates of poorly controlled chronic disease and premature mortality associated with poor heath than the Australian population as a whole. The need for a flexible, community based, culturally appropriate respite service in Alice Springs was identified and, after the service had been operating for 10 months, a qualitative evaluation was conducted to investigate the experiences of people involved in the use and operation of the service. METHODS: Semi-structured interviews were conducted with patients, carers, referrers, and stakeholders. A total of 20 people were interviewed. Interpretative Phenomenological Analysis was used inductively to analyse the transcripts. Two case studies are also described which illustrate in greater detail the impact the respite service has had on people’s lives. RESULTS: From the semi-structured interviews, two superordinate themes along with a number of sub themes were developed. The two superordinate themes described both “The Big Picture” considerations as well as the pragmatics of “Making the Service Work”. The sub themes highlighted issues such as being stuck at home and the relief that respite provided. The case studies poignantly illustrate the difference the respite service made to the quality of life of two patients. DISCUSSION: The findings clearly indicate an improvement in quality of life for respite patients and their carers. The respite service enabled improved care coordination of chronic and complex patients as well as improved medication compliance and symptom management. As a result of this evaluation a number of recommendations to continue and improve the service are provided.